Usage Effect of E-Government - Gebby Soean; Grace T. Pontoh; Syamsuddin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study uses the UTAUT model. The UTAUT model is a model that explains user behavior towards new information technology. This study aims to analyze the influence of performance expectancy, effort expectancy, social influences, facilitating conditions on the use of SIPD. This research was conducted in the North Morowali Regency Government with a total sample of 40 SIPD users. This study uses primary data, the data collection method is done by distributing questionnaires with the survey method . The statistical method used to test the hypothesis is to use the Structural Equation Model (SEM), which is a data analysis tool using Smart-PLS 3.0. The results of this study indicate that performance expectancy have a positive effect on SIPD, effort expectancy have a positive effect on the use of SIPD, social influences have a positive effect on the use of SIPD, facilitating conditions have a positive effect on the use of SIPD .